Teaching of Mathematics in the initial years of Fundamental Teaching in Brazil: what the research presented in the XII ENEM-2016 (Research, Society and Development, 2018)
This paper presents a review of an ongoing postdoctoral research that seeks to identify and analyze the themes, methodologies and theoretical contributions of the productions related to the teaching of Mathematics in the initial years of Elementary Education and the training of its teachers. The purpose of this article is to establish the themes and theoretical and methodological approaches worked in the productions that deal with the teaching of Mathematics in the initial years of Elementary Education and the formation of its teachers, starting from the works presented in the XII ENEM / 2016. Using documentary research and the state of the art or state of the art methodology, a cut was made in 6 of the 25 proposed axes at the Meeting, analyzing 205 works related to the focus of our research. We present in this article, the 30 works of the Axis Conceptions, Beliefs and Attitudes in Mathematics Education. Initially it was verified that only 5 of them dealt with Mathematics in the initial years of Elementary School and, among these, we delimited only 2, dealing directly with teaching and learning. The analyzes carried out in these works allowed to perceive a greater concern with the teacher training and its practice in the teaching of Mathematics, without concentration of themes or contents, as we expected. We conclude that challenges and possibilities are presented in the discussions offered in the analyzed works, also showing new updated trends and theoretical references. In this sense, the presentation of papers in meetings and congresses in the area, with discussions about the conceptions of teachers and trainers of teachers who teach mathematics, in the different contexts in which they live their practices, can contribute to the improvement in the teaching and learning of Mathematics.